Teriparatide improves early callus formation in distal radial fractures: Analysis of a subgroup of patients within a randomized trial - Aspenberg, Per (Informa Healthcare, 2010)
Background Teriparatide (parathyreoid hormone; PTH 1-34) increases skeletal mass in humans and improves fracture healing in animals. A recent randomized multicenter trial of nonoperated distal radial fractures showed a moderate shortening of the time to restoration of cortical continuity by treatment with 20 μg (low-dose) teriparatide per day, but not with 40 μg (high-dose). As radiographic cortical continuity appears late in the healing process, perhaps too late for clinical relevance, we studied the qualitative appearance of the callus 5 weeks after fracture. Methods One third of the patients of the international trial were treated at Linköping University Hospital. The multicenter trial did not evaluate early callus formation. We therefore made a blinded qualitative scoring of the callus at 5 weeks in our 27 patients. Callus formation was arbitrarily classified as rich, intermediate, or poor. Results 9 patients were classified as rich (none had received placebo, 3 low-dose teriparatide, and 6 high-dose teriparatide). 9 patients were classified as intermediate (1 had received placebo, 5 low-dose, and 3 high-dose). 9 patients were classified as poor (7 had received placebo, 1 low-dose, and 1 high-dose) (p < 0.001). Interpretation This is a post hoc subgroup analysis of an outcome variable, which was not in the official protocol. The results must therefore be interpreted with caution. However, in combination with the results of the larger trial, the data suggest that radiographic quality at an early time point might be a sensitive variable, perhaps better than time to cortical continuity. Moreover, teriparatide appeared to improve early callus formation in distal radial fractures.